A simple method for fabricating custom sectional impression trays for making definitive impressions in patients with microstomia - Bachhav, Vinay Chila; Aras, Meena Ajay (European Journal of Dentistry, 2012)
Objectives: A maximum mouth opening that is smaller than the size of a complete denture can make prosthetic treatment challenging. This article describes a simple technique used to fabricate maxillary and mandibular custom sectional impression trays for making definitive impressions in patients with microstomia. (Eur J Dent 2012;6:244-247)
Keywords: Dental impression technique; microstomia; definitive impression; sectional impression trays